ANALYSIS OF BUDGET PERFORMANCE: SPENDING VARIANCE, BUDGET REVISION AND BUDGET BLOCKING - Ramdany Ramdany; Aqliana Chaeriyyah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2023)
The purpose of this study is to ascertain the impact of changes in government expenditures, budget revisions, and budget blockages on Indonesia's Work Plan and Budget of Ministries/Agencies (RKA-K/L) implementation's performance value from 2016 to 2020. The study was conducted on 12 Ministries/Institutions (K/L) with a quantitative descriptive approach. Data analysis used descriptive statistics and the method of Structural Equation Modeling (SEM). The results of the study indicate that budget revisions and budget blockages affect the budget performance value of Ministries/Agencies (RKA-K/L) with the variance of Government spending as an intervening variable. The results of this study are expected to be used in decision-making, especially in the policy of budget revisions and budget blockades carried out by the Central Government and internal Ministries/Agencies (K/L) to reduce the widening of variance in human resources expenditures, goods expenditures, and capital expenditures which have an impact on performance achievement organization.